Analisis Pengelolaan Sampah dan Willingness To Pay (WTP) Masyarakat di Desa Purwasari - Mochammad Faroz Daq; Prayoga Suryadharma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Garbage is an endless problem to be discussed because every activity will definitely produce rubbish and so it happens in Purwasari Village. The habit of burning rubbish and the problem in the waste management are the main problems in Purwasari Village. The purpose of this study was to determine the community's waste management and Willingness to Pay (WTP) system for waste management efforts in Purwasari Village. The research uses qualitative research method with descriptive observational design. Research techniques carried out by means of field surveys, open interviews, and literature studies. The results of the study stated that waste management in the village was still inadequate due to the lack of land for the construction of temporary shelters and landfills and the low level of public awareness of the importance of managing waste properly and correctly. Suggestions that can be given are by conducting socialization about good and correct waste management and entering the budget for land acquisition that will be used for temporary shelters and final disposal. Keywords : Garbage, waste management, willingness to pay.